THE EFFECT OF USING VISUAL VIDEOS FOR LEARNING BASIC SWIMMING TECHNIQUES AND PUSH UP EXERCISES ON SWIMMING BREASTSTROKE ABILITY AT STATE 1 SINGKIL PRIMARY SCHOOL - Maqhfira Laili Syafitri Zega (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study entitled: “The effect of using visual video on learning basic butterfly swimming techniques with push-up exercises at SDN 1 SINGKIL” This study aims to determine the effects of using visual videos on learning basic butterfly swimming techniques with push-up exercises at SDN 1 SINGKIL the formulation of the problem in this study is: Is there any effect of the use of visual videos on learning the basic technique of swimming the butterfly style with push up exercises at SDN 1 SINGKIL? The method used in this research is quantitative. Certain pretest-posttest populations in this study were students in class 5A at SDN 1 SINGKIL in 2022/2023, totaling 20 students. The sampling technique is cluster sampling. The data collection technique used was the basic butterfly stroke technique test. The data analysis technique used is to calculate the average value(mean), standard deviation and the two-mean difference tet(t.test). Based on the results of the study, there was an effect of using visual videos on learning the basic techniques of butterfly stroke swimming with push-up exercises influenced by several other factors, only 22,6 % of the basic techniques of butterfly stroke swimming were influenced by push-up exercises.